Large effective population size masks population genetic structure in Hirondellea amphipods within the deepest marine ecosystem, the Mariana Trench - Stuart B. Piertney; Marius Wenzel; Alan J. Jamieson (Molecular Ecology, 2023)
The examination of genetic structure in the deep‐ocean hadal zone has focused on divergence between tectonic trenches to understand how environment and geography may drive species divergence and promote endemism. There has been little attempt to examine localized genetic structure within trenches, partly because of logistical challenges associated with sampling at an appropriate scale, and the large effective population sizes of species that can be sampled adequately may mask underlying genetic structure. Here we examine genetic structure in the superabundant amphipod Hirondellea gigas in the Mariana Trench at depths of 8126–10,545 m. RAD sequencing was used to identify 3182 loci containing 43,408 single nucleotide polymorphisms (SNPs) across individuals after stringent pruning of loci to prevent paralogous multicopy genomic regions being erroneously merged. Principal components analysis of SNP genotypes resolved no genetic structure between sampling locations, consistent with a signature of panmixia. However, discriminant analysis of principal components identified divergence between all sites driven by 301 outlier SNPs in 169 loci and significantly associated with latitude and depth. Functional annotation of loci identified differences between singleton loci used in analysis and paralogous loci pruned from the data set and also between outlier and nonoutlier loci, all consistent with hypotheses explaining the role of transposable elements driving genome dynamics. This study challenges the traditional perspective that highly abundant amphipods within a trench form a single panmictic population. We discuss the findings in relation to eco‐evolutionary and ontogenetic processes operating in the deep sea, and highlight key challenges associated with population genetic analysis in nonmodel systems with inherent large effective population sizes and genomes.

Scavenging amphipods from the Wallaby-Zenith Fracture Zone: Extending the hadal paradigm beyond subduction trenches - Johanna N. J. Weston; Rachael A. Peart; Heather A. Stewart; Heather Ritchie; Stuart B. Piertney; Thomas D. Linley; Alan J. Jamieson (Marine Biology, 2021)
Our understanding of the ecology of the hadal zone (> 6000 m depth) is based solely on subduction trenches, leaving other geomorphological features, such as fracture zones, troughs, and basins, understudied. To address this knowledge gap, the Wallaby-Zenith Fracture Zone, Indian Ocean (WZFZ; ~ 22°S, 102°E; maximum depth 6625 m measured during Expedition SO258) was studied using free-fall baited landers. We assessed the amphipod distribution and community assemblage of this non-subduction hadal feature and compared it to subduction hadal features. Eleven species were identified across the abyssal-hadal transition zone using a paired morphological and DNA barcoding approach. The community composition was found to change gradually from abyssal to hadal depths, which contrasts with the ecotone shift characteristic of subduction trenches. A large population of Bathycallisoma schellenbergi (Birstein & Vinogradov, 1958), a quintessential hadal amphipod, was present at the flat bottom of the WZFZ. Further, an mtDNA phylogeny resolved a degree of phylogeographic structure between the B. schellenbergi WZFZ population and four previously sampled Pacific Ocean subduction trench populations, indicating these features are not interconnected through ongoing gene flow. Combined, these data indicate that some amphipods have far broader distributions than previously understood, with some species present in both hadal subduction trenches and non-subduction fracture zones and basins interspersed across the abyssal plains. This initial exploration highlights that whilst non-subduction features are an overlooked minor fraction of the total hadal area, they are essential to our understanding of the ecological and evolutionary dynamics across the hadal zone.

Extended Pelagic Life in a Bathybenthic Octopus - Roger Villanueva; Vladimir V. Laptikhovsky; Stuart B. Piertney; Fernando Ángel Fernández-Álvarez; Martin A. Collins; Jonathan D. Ablett; Alejandro Escánez (Frontiers in Marine Science, 2020)
Planktonic stages of benthic octopuses can reach relatively large sizes in some species, usually in oceanic, epipelagic waters while living as part of the macroplankton. These young octopuses appear to delay settlement on the seabed for an undetermined period of time that is probably longer than for those octopus paralarvae living in coastal, neritic waters. The reason for this delay is unknown and existing information about their biology is very scarce. Here we report on the presence of juvenile and subadult forms of the bathybenthic octopus Pteroctopus tetracirrhus in oceanic waters of the South and North Atlantic and its association with the pyrosomid species Pyrosoma atlanticum , apparently used by the octopus as a refuge or shelter. The relatively large size of the P. tetracirrhus living in oceanic waters as the individuals reported here, together with the morphological characteristics of this bathybenthic species including its gelatinous body, minute suckers embedded in swollen skin and the deep interbrachial web, indicates that P. tetracirrhus may be considered a model of a transitional octopus species that is colonizing the pelagic environment by avoiding descending to the bathyal benthos. This process seems to occur in the same way as in the supposed origin of the ctenoglossan holopelagic octopods of the families Amphitretidae, Bolitaenidae, and Vitreledonellidae, which have arisen via neoteny from the planktonic paralarval stages of benthic octopuses.

Adaptive and neutral genetic differentiation among Scottish and endangered Irish red grouse (Lagopus lagopus scotica) - Yvonne Meyer-Lucht; Kevin P. Mulder; Marianne C. James; Barry J. McMahon; Kieran Buckley; Stuart B. Piertney; Jacob Höglund (Conservation Genetics, 2016)

The role of parasite‐driven selection in shaping landscape genomic structure in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Alex Douglas; Marianne C. James; Steve M. Redpath; Stuart B. Piertney (Molecular Ecology, 2016)
Landscape genomics promises to provide novel insights into how neutral and adaptive processes shape genome‐wide variation within and among populations. However, there has been little emphasis on examining whether individual‐based phenotype–genotype relationships derived from approaches such as genome‐wide association (GWAS) manifest themselves as a population‐level signature of selection in a landscape context. The two may prove irreconcilable as individual‐level patterns become diluted by high levels of gene flow and complex phenotypic or environmental heterogeneity. We illustrate this issue with a case study that examines the role of the highly prevalent gastrointestinal nematode Trichostrongylus tenuis in shaping genomic signatures of selection in red grouse ( Lagopus lagopus scotica ). Individual‐level GWAS involving 384 SNPs has previously identified five SNPs that explain variation in T. tenuis burden. Here, we examine whether these same SNPs display population‐level relationships between T. tenuis burden and genetic structure across a small‐scale landscape of 21 sites with heterogeneous parasite pressure. Moreover, we identify adaptive SNPs showing signatures of directional selection using outlier analysis and relate population‐ and individual‐level patterns of multilocus neutral and adaptive genetic structure to T. tenuis burden. The five candidate SNPs for parasite‐driven selection were neither associated with T. tenuis burden on a population level, nor under directional selection. Similarly, there was no evidence of parasite‐driven selection in SNPs identified as candidates for directional selection. We discuss these results in the context of red grouse ecology and highlight the broader consequences for the utility of landscape genomics approaches for identifying signatures of selection.

Gene dynamics of toll-like receptor 4 through a population bottleneck in an insular population of water voles (Arvicola amphibius) - Martha K. Gavan; Matthew K. Oliver; Alex Douglas; Stuart B. Piertney (Conservation Genetics, 2015)

Erratum to: Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2015)

Genome‐wide association and genome partitioning reveal novel genomic regions underlying variation in gastrointestinal nematode burden in a wild bird - Marius A. Wenzel; Marianne C. James; Alex Douglas; Stuart B. Piertney (Molecular Ecology, 2015)
Identifying the genetic architecture underlying complex phenotypes is a notoriously difficult problem that often impedes progress in understanding adaptive eco‐evolutionary processes in natural populations. Host–parasite interactions are fundamentally important drivers of evolutionary processes, but a lack of understanding of the genes involved in the host's response to chronic parasite insult makes it particularly difficult to understand the mechanisms of host life history trade‐offs and the adaptive dynamics involved. Here, we examine the genetic basis of gastrointestinal nematode ( Trichostrongylus tenuis ) burden in 695 red grouse ( Lagopus lagopus scotica ) individuals genotyped at 384 genome‐wide SNPs. We first use genome‐wide association to identify individual SNPs associated with nematode burden. We then partition genome‐wide heritability to identify chromosomes with greater heritability than expected from gene content, due to harbouring a multitude of additive SNPs with individually undetectable effects. We identified five SNPs on five chromosomes that accounted for differences of up to 556 worms per bird, but together explained at best 4.9% of the phenotypic variance. These SNPs were closely linked to genes representing a range of physiological processes including the immune system, protein degradation and energy metabolism. Genome partitioning indicated genome‐wide heritability of up to 29% and three chromosomes with excess heritability of up to 4.3% (total 8.9%). These results implicate SNPs and novel genomic regions underlying nematode burden in this system and suggest that this phenotype is somewhere between being based on few large‐effect genes (oligogenic) and based on a large number of genes with small individual but large combined effects (polygenic).

In silico identification and characterisation of 17 polymorphic anonymous non-coding sequence markers (ANMs) for red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Stuart B. Piertney (Conservation Genetics Resources, 2015)

Identification and characterisation of 17 polymorphic candidate genes for response to parasitic nematode (Trichostrongylus tenuis) infection in red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; Stuart B. Piertney (Conservation Genetics Resources, 2015)

Fine‐scale population epigenetic structure in relation to gastrointestinal parasite load in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Stuart B. Piertney (Molecular Ecology, 2014)
Epigenetic modification of cytosine methylation states can be elicited by environmental stresses and may be a key process affecting phenotypic plasticity and adaptation. Parasites are potent stressors with profound physiological and ecological effects on their host, but there is little understanding in how parasites may influence host methylation states. Here, we estimate epigenetic diversity and differentiation among 21 populations of red grouse ( Lagopus lagopus scotica ) in north‐east Scotland and test for association of gastrointestinal parasite load (caecal nematode Trichostrongylus tenuis ) with hepatic genome‐wide and locus‐specific methylation states. Following methylation‐sensitive AFLP (MSAP), 129 bands, representing 73 methylation‐susceptible and 56 nonmethylated epiloci, were scored across 234 individuals. The populations differed significantly in genome‐wide methylation levels and were also significantly epigenetically ( F SC = 0.0227; P F SC = 0.0058; P F ST outliers) using bayescan software and significant positive and negative association of 35 methylation states with parasite load from bespoke generalized estimating equations (GEE), simple logistic regression ( sam ) and Bayesian environmental analysis ( bayenv 2). Following Sanger sequencing, genome mapping and geneontology ( go ) annotation, some of these epiloci were linked to genes involved in regulation of cell cycle, signalling, metabolism, immune system and notably rRNA methylation, histone acetylation and small RNAs. These findings demonstrate an epigenetic signature of parasite load in populations of a wild bird and suggest intriguing physiological effects of parasite‐associated cytosine methylation.

Corrigendum to Cameron et al . 2013 - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)

Eco‐evolutionary dynamics in response to selection on life‐history - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)
Understanding the consequences of environmental change on ecological and evolutionary dynamics is inherently problematic because of the complex interplay between them. Using invertebrates in microcosms, we characterise phenotypic, population and evolutionary dynamics before, during and after exposure to a novel environment and harvesting over 20 generations. We demonstrate an evolved change in life‐history traits (the age‐ and size‐at‐maturity, and survival to maturity) in response to selection caused by environmental change (wild to laboratory) and to harvesting (juvenile or adult). Life‐history evolution, which drives changes in population growth rate and thus population dynamics, includes an increase in age‐to‐maturity of 76% (from 12.5 to 22 days) in the unharvested populations as they adapt to the new environment. Evolutionary responses to harvesting are outweighed by the response to environmental change (~ 1.4 vs. 4% change in age‐at‐maturity per generation). The adaptive response to environmental change converts a negative population growth trajectory into a positive one: an example of evolutionary rescue.

Individual variation in dispersal associated with phenotype influences fine-scale genetic structure in weasels - Allan D. McDevitt; Matthew K. Oliver; Stuart B. Piertney; Paulina A. Szafrańska; Marek Konarzewski; Karol Zub (Conservation Genetics, 2013)

A transcriptomic investigation of handicap models in sexual selection - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; François Mougeot; Jesús Martínez-Padilla; Stuart B. Piertney (Behavioral Ecology and Sociobiology, 2013)

Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2012)

Genetic variation among endangered Irish red grouse (Lagopus lagopus hibernicus) populations: implications for conservation and management - Barry J. McMahon; Magnus P. Johansson; Stuart B. Piertney; Kieran Buckley; Jacob Höglund (Conservation Genetics, 2012)

Survey and management of mussel Mytilus species in Scotland - Patricia Joanna Dias; Stuart B. Piertney; Mike Snow; Ian M. Davies (Hydrobiologia, 2011)

Fine-scale genetic structure of bottlenose dolphins, Tursiops truncatus, in Atlantic coastal waters of the Iberian Peninsula - Ruth Fernández; M. Begoña Santos; Graham J. Pierce; Ángela Llavona; Alfredo López; Mόnica A. Silva; Marisa Ferreira; Manuel Carrillo; Pablo Cermeño; Santiago Lens; Stuart B. Piertney (Hydrobiologia, 2011)

Frontiers in host–parasite ecology and evolution - STEVE PATERSON; STUART B. PIERTNEY (Molecular Ecology, 2011)

Characterising functionally important and ecologically meaningful genetic diversity using a candidate gene approach - Stuart B. Piertney; Lucy M. I. Webster (Genetica, 2010)

Ecological, morphological and genetic divergence of sympatric North Atlantic killer whale populations - ANDREW D. FOOTE; JASON NEWTON; STUART B. PIERTNEY; ESKE WILLERSLEV; M. THOMAS P. GILBERT (Molecular Ecology, 2009)
Ecological divergence has a central role in speciation and is therefore an important source of biodiversity. Studying the micro‐evolutionary processes of ecological diversification at its early stages provides an opportunity for investigating the causative mechanisms and ecological conditions promoting divergence. Here we use morphological traits, nitrogen stable isotope ratios and tooth wear to characterize two disparate types of North Atlantic killer whale. We find a highly specialist type, which reaches up to 8.5 m in length and a generalist type which reaches up to 6.6 m in length. There is a single fixed genetic difference in the mtDNA control region between these types, indicating integrity of groupings and a shallow divergence. Phylogenetic analysis indicates this divergence is independent of similar ecological divergences in the Pacific and Antarctic. Niche‐width in the generalist type is more strongly influenced by between‐individual variation rather than within‐individual variation in the composition of the diet. This first step to divergent specialization on different ecological resources provides a rare example of the ecological conditions at the early stages of adaptive radiation.

Landscape barriers reduce gene flow in an invasive carnivore: geographical and local genetic structure of American mink in Scotland - ANDRZEJ ZALEWSKI; STUART B. PIERTNEY; HANNA ZALEWSKA; XAVIER LAMBIN (Molecular Ecology, 2009)
To be effective, management programmes geared towards halting or reversing the spread of invasive species must focus on defined and defensible areas. This requires knowledge of the dispersal of non‐native species targeted for control to better understand invasion and recolonisation scenarios. We investigated the genetic structure of invasive American mink ( Neovison vison ) in Scotland, and incorporated landscape genetic approaches to examine resultant patterns in relation to geographical features that may influence dispersal. Populations of mink sampled from 10 sites in two regions (Argyll and Northeast Scotland) show a distinct genetic structure. First, the majority of pairwise population comparisons yielded F ST values that were significantly greater than zero. Second, amova revealed that most of the genetic variance was attributable to differences among regions. Assignment tests placed 89 or more of individuals into their sampled region. Bayesian clustering methods grouped samples into two clusters according to their region of origin. Wombling approach identified the Cairngorms Mountains as a major impediment to gene flow between the regions. Mantel pairwise correlations between genetic and geographical distances estimated as least‐cost distance assuming a linear increase in the cost of movement with increasing elevation were higher than Euclidean distances or distance along waterways. Spatial autocorrelation analyses revealed stronger spatial structuring for females than for males. These results suggest that gene flow by American mink is restricted by landscape features (mountain ranges) and that eradication attempt should in the first instance break down the connectivity between management units separated by mountains.

Spatio‐temporal variation in the strength and mode of selection acting on major histocompatibility complex diversity in water vole ( Arvicola terrestris ) metapopulations - MATTHEW K. OLIVER; XAVIER LAMBIN; THOMAS CORNULIER; STUART B. PIERTNEY (Molecular Ecology, 2009)
Patterns of spatio‐temporal genetic variation at a class II major histocompatibility complex (MHC) locus and multiple microsatellite loci were analysed within and between three water vole metapopulations in Scotland, UK. Comparisons of MHC and microsatellite spatial genetic differentiation, based on standardised tests between two demographically asynchronous zones within a metapopulation, suggested that spatial MHC variation was affected by balancing selection, directional selection and random genetic drift, but that the relative effects of these microevolutionary forces vary temporally. At the metapopulation level, between‐year differentiation for MHC loci was significantly correlated with that of microsatellites, signifying that neutral factors such as migration and drift were primarily responsible for overall temporal genetic change at the metapopulation scale. Between metapopulations, patterns of genetic differentiation implied that, at large spatial scales, MHC variation was primarily affected by directional selection and drift. Levels of MHC heterozygosity in excess of Hardy–Weinberg expectations were consistent with overdominant balancing selection operating on MHC variation within metapopulations. However, this effect was not constant among all samples, indicating temporal variation in the strength of selection relative to other factors. The results highlight the benefit of contrasting variation at MHC with neutral markers to separate the effects of stochastic and deterministic microevolutionary forces, and add to a growing body of evidence showing that the mode and relative strength of selection acting on MHC diversity varies both spatially and temporally.

Spatial distribution of mitochondrial and microsatellite DNA variation in Daubenton's bat within Scotland - THONGCHAI NGAMPRASERTWONG; IAIN J. MACKIE; PAUL A. RACEY; STUART B. PIERTNEY (Molecular Ecology, 2008)
Daubenton's bat ( Myotis daubentonii ) is a known reservoir for European bat lyssavirus type 2 (EBLV‐2). An appreciation of the potential for epidemiological spread and disease risk requires an understanding of the dispersal of the primary host, and any large‐scale geographical barriers that may impede gene flow. The spatial pattern of microsatellite and mitochondrial DNA variation was examined to infer patterns of dispersal of bats among 35 populations across Scotland. DNA sequence variation at the mitochondrial control region and ND1 genes revealed two distinct phylogeographical clades, with generally nonoverlapping geographical distributions except for a small number of populations where both matrilines were found in sympatry. Such discontinuity suggests that Scotland was recolonised twice following the retreat of the Pleistocene ice sheet with little subsequent matrilineal introgression. However, eight microsatellite loci showed low levels of genetic divergence among populations, even between populations from the two distinct mitochondrial DNA clades. An overall, macrogeographical genetic isolation‐by‐distance pattern was observed, with high levels of gene flow among local populations. Apparently contrasting patterns of mitochondrial and microsatellite divergence at different scales could be explained by sex‐specific differences in gene flow at large scales.

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Isolation and characterization of a MHC class II DRB locus in the European water vole (Arvicola terrestris) - Matthew K. Oliver; Stuart B. Piertney (Immunogenetics, 2006)

Phylogeographic structure and postglacial evolutionary history of water voles ( Arvicola terrestris ) in the United Kingdom - STUART B. PIERTNEY; WENDY A. STEWART; XAVIER LAMBIN; SANDRA TELFER; JON AARS; JOHN F. DALLAS (Molecular Ecology, 2005)
The phylogeographic pattern of mitochondrial DNA variation in water voles ( Arvicola terrestris ) from 57 localities across the United Kingdom and representative samples from Spain, France, Switzerland and Finland was determined from sequence variation in the central portion of the control region. Twenty‐seven different haplotypes were resolved which formed two distinct phylogenetic clades. This major division separated haplotypes found in Scotland from those found in England and Wales. Nested clade analysis of haplotypes indicated that such a division was a consequence of allopatric fragmentation. The haplotypes found in Switzerland, France and Spain clustered with Scottish haplotypes, whereas the haplotype from Finland clustered with the English/Welsh haplotypes. These patterns indicate that contemporary Scottish populations are derived from an Iberian glacial refugium, whereas English and Welsh populations are derived from an eastern European refugium. As such, the postglacial recolonization of the United Kingdom must have involved two colonization events, either in different localities with no subsequent contact, or as two waves separated over time, with the second wave of colonizers displacing the first. An analysis of molecular variance ( amova ) identified significant population genetic divergence within both the major clades, indicative of restricted gene flow and regional population isolation. The implications of both phylogeographical and population genetic structure are discussed in context with the conservation of water voles in Britain.

Similar estimates of population genetic composition and sex ratio derived from carcasses and faeces of Eurasian otter Lutra lutra - John F. Dallas; Karen E. Coxon; Tim Sykes; Paul R. F. Chanin; Freda Marshall; David N. Carss; Philip J. Bacon; Stuart B. Piertney; Paul A. Racey (Molecular Ecology, 2003)
Collecting faeces is viewed as a potentially efficient way to sample elusive animals. Nonetheless, any biases in estimates of population composition associated with such sampling remain uncharacterized. The goal of this study was to compare estimates of genetic composition and sex ratio derived from Eurasian otter Lutra lutra spraints (faeces) with estimates derived from carcasses. Twenty per cent of 426 wild‐collected spraints from SW England yielded composite genotypes for 7–9 microsatellites and the SRY gene. The expected number of incorrect spraint genotypes was negligible, given the proportions of allele dropout and false allele detection estimated using paired blood and spraint samples of three captive otters. Fifty‐two different spraint genotypes were detected and compared with genotypes of 70 otter carcasses from the same area. Carcass and spraint genotypes did not differ significantly in mean number of alleles, mean unbiased heterozygosity or sex ratio, although statistical power to detect all but large differences in sex ratio was low. The genetic compositions of carcass and spraint genotypes were very similar according to confidence intervals of θ and two methods for assigning composite genotypes to groups. A distinct group of approximately 11 carcass and spraint genotypes was detected using the latter methods. The results suggest that spraints can yield unbiased estimates of population genetic composition and sex ratio.

Spatially restricted gene flow and reduced microsatellite polymorphism in the Eurasian otter Lutra lutra in Britain - John F. Dallas; Freda Marshall; Stuart B. Piertney; Philip J. Bacon; Paul A. Racey (Conservation Genetics, 2002)

Sex identification of the Eurasian otter Lutra lutra by PCR typing of spraints - John F. Dallas; David N. Carss; Freda Marshall; Klaus-Peter Koepfli; Hans Kruuk; Philip J. Bacon; Stuart B. Piertney (Conservation Genetics, 2000)

Isolation and characterization of microsatellite loci in the freshwater gastropod, Biomphalaria glabrata , an intermediate host for Schistosoma mansoni - Catherine S. Jones; Anne E. Lockyer; David Rollinson; Stuart B. Piertney; Leslie R. Noble (Molecular Ecology, 1999)

Local genetic structure in red grouse ( Lagopus lagopus scoticus ): evidence from microsatellite DNA markers - STUART B. PIERTNEY; ANDREW D. C. MACCOLL; PHILIP J. BACON; JOHN F. DALLAS (Molecular Ecology, 1998)
Allelic variation at seven hypervariable tri‐ and tetranucleotide microsatellite loci was used to determine levels of population differentiation between 14 populations of red grouse ( Lagopus lagopus scoticus ) in northeast Scotland, UK. Despite the potential for long‐distance dispersal in grouse, and a semicontinuous habitat, significant population divergence was observed (mean R ST = 0.153; P P